Model Website I-Care sebagai Inovasi Media Bimbingan Asertif untuk Mencegah Pelecehan Seksual di Kalangan Siswa SMA - Desi Ratna Sari; Abdul Saman; Sahril Buchori (Technocouns: Journal of Technology in Guidance and Counseling, 2025)
The aims of this research are to develop students' assertive abilities, (2) Prototype of I-Care website media to develop students' assertive abilities, (3) Validity of I-Care website media to develop students' assertive abilities, and (4) Practicality of I-Care website media to develop students' assertive abilities. This research utilizes the Research and Development (RnD) method with an adaptation of the Borg and Gall model. The data analysis techniques applied include content analysis for qualitative data and descriptive analysis for quantitative data. The research results reveal that: (1) students need assertive information service media to prevent acts of sexual harassment, but until now there is no such service media at school. (2) Assertive information service media in the form of the I-Care Website is expected to be a solution for providing assertive information service media, (3) The assertive information service media developed has been validated by experts, and (4) This media shows results in the very practical category based on expert tests and small group trials. Therefore, the I-Care Website is considered very suitable as a supporting medium for assertive guidance services for students.